Enhancing the oxygen ionic conductivity of (111) oriented Ce0.80Sm0.20O2-δ thin film through strain engineering. (20th June 2017) - Arunkumar, P.; Panda, Padmalochan; Sribalaji, M.; Ramaseshan, R.; Keshri, Anup Kumar; Babu, K. Suresh
Graphical abstract: Abstract: Several physicochemical properties can be tailored by tuning the lattice strain of the crystal. Here, we report the effect of lattice strain on oxygen ion conduction of oriented samarium doped ceria (SDC) films deposited over an amorphous quartz substrate. Lattice distortion was induced by varying the deposition rate in electron beam deposition technique (EB-PVD). Texture coefficient calculation and pole figure analysis confirms the (111) orientation in out‐off plane direction. Stress state was monitored using sin 2 Ψ method in tri-axial direction and the results indicate a reduction in compressive stress with an increase in deposition rate. A difference in the mean free path of adatom influences the surface morphology of SDC films with compressive stress leading to a significant impact on conductivity. Compared to higher compressive stress, thin film containing lower stress along (111) orientation exhibited a two order enhancement in conductivity. The faster ionic conductivity arises from the ease of oxygen ion hopping through the expanded lattice as compared to the highly-stressed crystal structure. Thus, the deposition rate in EB-PVD provides a valuable technique for engineering the strain to realize the potential enhancement in the efficiency of electrolyte for ITSOFC application.